2021
DOI: 10.1177/21649561211053828
|View full text |Cite
|
Sign up to set email alerts
|

“Then COVID happened…”: Veterans’ Health, Wellbeing, and Engagement in Whole Health Care During the COVID-19 Pandemic

Abstract: Background Little is known about the COVID-19 pandemic’s impact on US military veterans’ health, wellbeing, and care engagement. Healthcare systems like VA need additional information about the pandemic’s biopsychosocial impacts and how a Whole Health approach may help to address them. Objective To examine how the pandemic has affected veterans’ health, wellbeing, and engagement in the VA Whole Health System of Care. Method We conducted qualitative interviews with 40 veterans at a large multicampus VA healthca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 40 publications
1
9
0
1
Order By: Relevance
“…Loneliness is often a concern among older adults, particularly among individuals with low socioeconomic status [ 11 ], and social isolation and loneliness are associated with increased morbidity and mortality [ 12 ], even outside the context of a global pandemic. Older veterans indicated that the pandemic increased loneliness and sorrow due to the isolation and disruption of their ordinary routines [ 13 ], and researchers also found that a lack of social support and increasing numbers of pandemic-related stressors were associated with mental health difficulties [ 14 ]. In a national sample of US veterans, the pre- to peripandemic prevalence of generalized anxiety disorder increased from 7.1% to 9.4%, with the most pronounced increase observed in veterans aged 45-64 years (8.2% to 13.5%) [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…Loneliness is often a concern among older adults, particularly among individuals with low socioeconomic status [ 11 ], and social isolation and loneliness are associated with increased morbidity and mortality [ 12 ], even outside the context of a global pandemic. Older veterans indicated that the pandemic increased loneliness and sorrow due to the isolation and disruption of their ordinary routines [ 13 ], and researchers also found that a lack of social support and increasing numbers of pandemic-related stressors were associated with mental health difficulties [ 14 ]. In a national sample of US veterans, the pre- to peripandemic prevalence of generalized anxiety disorder increased from 7.1% to 9.4%, with the most pronounced increase observed in veterans aged 45-64 years (8.2% to 13.5%) [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…In some cases, the social connections served as a conduit for the knowledge and skills that the group sought to instil. It is also important to note that the interactions and relationships at the heart of TCMLH might have provided a much‐needed lifeline to Veterans who were socially isolated during early days of the pandemic 32 . All of these findings are consistent with the larger literature that showcases the benefits of peers as health coaches and patient navigators for health engagement, 33–35 as well as the power of peer support to counteract social isolation, including in the times of the COVID‐19 pandemic 36 .…”
Section: Discussionmentioning
confidence: 99%
“…Management of these conditions frequently require more, rather than less, interaction with providers and significant others. However, there is scarce information regarding veterans' perspectives on the effects of pandemic-related isolation on the management of their mental and physical health, including the management of chronic pain (Purcell et al, 2021).…”
Section: Rationale Informing the Projectmentioning
confidence: 99%